Critical issues in WTO safeguard jurisprudence for the conduct of safeguard investigations in Jamaica - Beckford, Delroy S. (2004)
Examines some of the recent WTO jurisprudence on safeguards and their implications for the conduct of safeguard investigations in Jamaica